Sex differences in 24-hour ultra-marathon performance - A retrospective data analysis from 1977 to 2012 (Clinics, 2014)
OBJECTIVES: This study examined the changes in running performance and the sex differences between women and men in 24-hour ultra-marathons held worldwide from 1977 to 2012. METHOD: Changes in running speed and ages of the fastest 24-hour ultra-marathoners were determined using single- and multi-level regression analyses. RESULTS: From 1977 to 2012, the sex differences in 24-hour ultra-marathon performance were 4.6±0.5% for all women and men, 13.3% for the annual fastest finishers, 12.9±0.8% for the top 10 and 12.2±0.4% for the top 100 finishers. Over time, the sex differences decreased for the annual fastest finishers to 17%, for the annual 10 fastest finishers to 11.3±2.2% and for the annual 100 fastest finishers to 14.2±1.8%. For the annual fastest men, the age of peak running speed increased from 23 years (1977) to 53 years (2012). For the annual 10 and 100 fastest men, the ages of peak running speed were unchanged at 40.9±2.5 and 44.4±1.1 years, respectively. For women, the ages of the annual fastest, the annual 10 fastest and the annual 100 fastest remained unchanged at 43.0±6.1, 43.2±2.6 and 43.8±0.8 years, respectively. CONCLUSION: The gap between the annual top, annual top 10 and annual top 100 female and male 24-hour ultra-marathoners decreased over the last 35 years; however, it seems unlikely that women will outrun men in 24-hour ultra-marathons in the near future. The fastest 24-hour ultra-marathoners worldwide achieved their peak performance at the age of master athletes (>;35 years).